Phorbol-12-myristate-13-acetate is a potent enhancer of B cells with a granzyme B+ regulatory phenotype - Veh, Johanna; Mangold, Charlotte; Felsen, Anja; Ludwig, Carolin; Gerstner, Lisa; Reinhardt, Peter; Schrezenmeier, Hubert; Fabricius, Dorit; Jahrsdörfer, Bernd (Frontiers in Immunology, 2023)
Introduction The infusion of ex-vivo-generated regulatory B cells may represent a promising novel therapeutic approach for a variety of autoimmune and hyperinflammatory conditions including graft-versus-host disease. Methods Previously, we developed a protocol for the generation of a novel population of regulatory B cells, which are characterized by secretion of enzymatically active granzyme B (GraB cells). This protocol uses recombinant interleukin 21 (IL-21) and goat-derived F(ab)’2 fragments against the human B cell receptor (anti-BCR). Generally, the use of xenogeneic material for the manufacturing of advanced therapy medicinal products should be avoided to prevent adverse immune reactions as well as potential transmission of so far unknown diseases. Results In the present work we demonstrated that phorbol-12-myristate-13-acetate (PMA/TPA), a phorbol ester with a particular analogy to the second messenger diacylglycerol (DAG), is a potent enhancer of IL-21-induced differentiation of pre-activated B cells into GraB cells. The percentage of GraB cells after stimulation of pre-activated B cells with IL-21 and PMA/TPA was not significantly lower compared to stimulation with IL-21 and anti-BCR. Discussion Given that PMA/TPA has already undergone encouraging clinical testing in patients with certain haematological diseases, our results suggest that PMA/TPA may be a safe and feasible alternative for ex-vivo manufacturing of GraB cells.